STUDY OF THE USE OF VORTEX PRESSURE APPARATUS FOR CLEAN WATER FROM SALT LOW-SOLUBILITY - , С. Е., А. В. (Municipal economy of cities. Series: «Economy science», 2013)
A study of the theoretical and empirical relationships that describe the stages of the process , determining the amount , the rate of growth and the kinetics of the formation of carbonaceous deposits. The results of operation of industrial and laboratory experiments mixing of sewage with different alkalinity , as well as the influence of the stirring speed while on the rate of formation of carbonaceous deposits. The opportunity of application - update themselves perfected horizontal -flow cylindrical hydrocyclone for Effective mixing wastewater with different chemical composition in order to clean water from temporary hardness salts .